Berry syndrome: First Successful neonatal single-stage repair in India - Shefali Yadav; Anil Bhan; Rajesh Sharma; Amit Misri; Akriti Gera; Pankaj Bajpai (Wolters Kluwer Medknow Publications, 2024)
Berry et al. (1982) described a rare syndrome associated with distal aortopulmonary window, aortic origin of the right pulmonary artery, intact ventricular septum, and interruption or coarctation of the aorta. Here, we present the first neonatal case of single-stage repair of Berry syndrome in India. Timely surgery and skilled postoperative care define the short-term and long-term outcomes. Single-staged repair is preferred wherever feasible.